Problemy polityki przeciwdziałania katastrofom naturalnym - case study - Kowary - Piepiora, Zbigniew (Problems of the Policy of Counteracting the Natural Catastrophes - Case Study - Kowary, 2008)
The aim of this article is to present some aspects of the problems of the natural catastrophes on a local level. The main task of the publication is an attempt to define the notion of the Policy of counteracting the natural disasters which according to the author is not quite recognized category in Poland. The case study of the Kowary municipal (NUTS 5) as an example of executing this policy on the local level is presented. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 411-418